Impact of Productive Waqf Management in Indonesia and Malaysia: Systematic Literature - Wahyudi Rusdi; Md Mahfujur Rahman; Moh Agus Nugroho (Institut Agama Islam Negeri Kendari, 2022)
In the management of productive waqf, Indonesia and Malaysia are countries that are quite serious in dealing with waqf issues. Both countries are also predominantly Muslim, so the impact of productive waqf management is certainly very helpful for the two countries' economies. Using the Systematic Literature Review (SLR) method to describe the impact of productive waqf management in Indonesia and Malaysia. There were 75 journals studied, filtered by timeline, type, language, country, topic and participant. Ten articles that meet the criteria. SLR identified that 90% of the population are Nazhir or waqf managers, which is a very important population for the success of productive waqf management. The agricultural management sector was the most widely used by Nazhir to maximize productive waqf with a percentage of 40%. The health sector, such as hospitals and clinics, became the productive waqf management sector which Nazhir often used to maximize income with a percentage of 30%. Then in the rental housing sector with a percentage of 20% and 10% in the minimarket or retail sector and others. The SLR method has identified a management system with a profit-sharing system, and investment allocation mapping is the method used by Nazhir.